THE OBJECTIVE LEARNING ENGLISH IN INDONESIA - Mutia Putri; Santoso, Didik (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The objective of learning English in Indonesia is to improve people's communication skills in English. English is an international language used in various fields, such as business, education, and technology. By having good English skills, Indonesian people can access wider opportunities in the global world, communicate with people from different countries, and broaden their knowledge and insight. Learning English is also crucial in today's world of work, as many companies seek employees with good English communication skills to face global competition. However, some people in Indonesia may need help understanding the importance of learning English. They may perceive English as a foreign language only needed in specific situations or focus solely on grammar and vocabulary. To address this, it is essential to emphasize the actual purpose of learning English in Indonesia. The Ministry of Education and Culture is vital in regulating the curriculum and standards for learning English in Indonesia. The objectives of learning English include developing knowledge and language skills, such as listening, speaking, reading, and writing, as well as grammar and vocabulary. Language skills should be actively applied in everyday life, enabling individuals to communicate effectively, understand written text, and express thoughts and ideas. Additionally, learning English aims to foster attitudes appropriate to the language's context and variety. To achieve these objectives, improving the quality of English language teaching in Indonesia, incorporating innovative methods and technology, and developing a relevant curriculum are necessary. By doing so, individuals in Indonesia can enhance their communication skills, overcome barriers, build intercultural relationships, and actively contribute to the international community.